(untitled) (LACCEI, 2024)
After two years of social isolation, the educational dynamics have to be re-adapted to a new face-to-face, where the demands and expect ations of the students are not the same as before. The professor continues to be an important part of learning, so his attitude and way of teaching could be linked to the effort of students to achieve their academic goals. Therefore, the main objective of the study was to know the relationship of the professor’s teaching style with the academic engagement of engineering students. The research was quantitative, correlational and non-experimental cross-sectional and the effective sample was made up of 167 engineering students from Lima, Peru. According to the results, the majority of professors present a formal and structured style, however it is the open style that presents a positive, high and significant correlation index with academic engagement and its own dimensions. Additionally, it has been seen that women present more engagement than men, as well as industrial engineering students.